2021
DOI: 10.1093/cdn/nzab124
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota–Targeted Nutritional Interventions Improving Child Growth in Low- and Middle-Income Countries: A Systematic Review

Abstract: The objective of this systematic literature review was to evaluate the efficacy of probiotic, prebiotic, and synbiotic interventions compared to control on improving growth outcomes of children living in low-and middle-income countries (LMICs). Probiotics had a beneficial effect on at least one of the growth outcomes in five out of the eleven included studies. Of these, three studies were conducted in undernourished children, one in healthy children, and one in children without a described health status. No ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 69 publications
2
14
0
Order By: Relevance
“…Undernourished children have been observed with immature, less diverse, and dysbiotic gut microbiota which might be modified using gut microbiota-targeted nutritional interventions (256). In a recent systemic review encompassing studies in low-and middle-income countries, probiotics and synbiotics were reported to have potential advantages to improve the growth of undernourished children (257). Similarly, Onubi et al (258) concluded in their systemic review that probiotics have the potential to improve child growth in developing countries and in under-nourished children.…”
Section: Effects Of Probiotics Prebiotics and Synbiotics In Undernutr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Undernourished children have been observed with immature, less diverse, and dysbiotic gut microbiota which might be modified using gut microbiota-targeted nutritional interventions (256). In a recent systemic review encompassing studies in low-and middle-income countries, probiotics and synbiotics were reported to have potential advantages to improve the growth of undernourished children (257). Similarly, Onubi et al (258) concluded in their systemic review that probiotics have the potential to improve child growth in developing countries and in under-nourished children.…”
Section: Effects Of Probiotics Prebiotics and Synbiotics In Undernutr...mentioning
confidence: 99%
“…In this context, the effect of prebiotics in undernourished is not supported by strong experimental evidence. Heuven et al (257) found no effect of prebiotics FIGURE 4 | Overview of the impact of a balance diet versus western diet on gut microbiota and immune system and potential roles of interventions such as prebiotics, probiotics and synbiotics on microbiota-immune axis. In general, a balance diet modulates gut immune system directly or indirectly through gut microbiota with a mix of pro-and anti-inflammatory signals so that the immune system stays alert to keep its defenses but also remain tolerant to unnecessary signals to avoid needless inflammation (A).…”
Section: Effects Of Probiotics Prebiotics and Synbiotics In Undernutr...mentioning
confidence: 99%
“…Studies using short term microbiota-targeted nutritional interventions (around 3-months) on healthy or malnourished under five children have shown increase in body weight (Surono et al, 2011;Kara et al, 2019;Kusumo et al, 2019;Mai et al, 2021); whereas, studies with longer duration of intervention (six months or more) documented significant improvement in linear growth (Saran et al, 2002;He et al, 2005). Our study achieved minimal duration (3-months) that is necessary for measurable effects on growth (Heuven et al, 2021), which might be one of the reasons it failed to show significant results.…”
Section: Discussionmentioning
confidence: 86%
“…Probiotics can influence gut barrier functions in various ways; these include controlling mucus production, preventing bacterial adhesion, enrichment of tight junctions, increasing cell survival, and inducing defense mechanisms (O'Flaherty et al, 2010;Bron et al, 2017). A systematic review by Heuven et al looked at the effects of intervention that targeted gut-microbiota to improve child growth in low-and middle-income countries; five out of eleven studies demonstrated beneficial effects of probiotics on one or more growth parameters (Heuven et al, 2021). Systematic reviews indicated that undernourished children received more benefits from the probiotic intervention than well-nourished children (Onubi et al, 2015;Heuven et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation